Anti-Cancer Effects of Epigenetics Drugs Scriptaid and Zebularine in Human Breast Adenocarcinoma Cells - Yap, Zhi H.; Kong, Wei Yang; Azeez, Abdur Rahmaan; Fang, Chee-Mun; Ngai, Siew Ching (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: High relapse and metastasis progression in breast cancer patients have prompted the need to explore alternative treatments. Epigenetic therapy has emerged as an attractive therapeutic strategy due to the reversibility of epigenome structures. Objective: This study investigated the anti-cancer effects of epigenetic drugs scriptaid and zebularine in human breast adenocarcinoma MDA-MB-231 and MCF-7 cells. Methods: First, the half maximal Inhibitory Concentration (IC50) of scriptaid and zebularine, and the combination of both drugs on human breast adenocarcinoma MDA-MB-231 cells were determined. Next, MDA-MB-231 and MCF-7 cells were treated with IC50 of scriptaid, zebularine and the combination of both. After IC50 treatments, the anti-cancer effects were evaluated via cell migration assay, cell cycle analysis and apoptotic studies which included histochemical staining and reverse-transcriptase polymerase chain reaction (RT-PCR) of the apoptotic genes. Results: Both epigenetic drugs inhibited cell viability in a dose-dependent manner with IC50 of 2 nM scriptaid, 8 μM zebularine and a combination of 2 nM scriptaid and 2 μM zebularine. Both MDA-MB-231 and MCF-7 cells exhibited a reduction in cell migration after the treatments. In particular, MDA-MB-231 cells exhibited a significant reduction in cell migration (p < 0.05) after the treatments of zebularine and the combination of scriptaid and zebularine. Besides, cell cycle analysis demonstrated that scriptaid and the combination of both drugs could induce cell cycle arrest at the G0/G1 phase in both MDA-MB-231 and MCF-7 cells. Furthermore, histochemical staining allowed the observation of apoptotic features, such as nuclear chromatin condensation, cell shrinkage, membrane blebbing, nuclear chromatin fragmentation and cytoplasmic extension, in both MDA-MB-231 and MCF-7 cells after the treatments. Further, apoptotic studies revealed the upregulation of pro-apoptotic Bax, downregulation of anti-apoptotic Bcl-2 and elevation of Bax/Bcl-2 ratio in MDA-MB-231 cells treated with zebularine and MCF-7 cells treated with all drug regimens. Conclusion: Collectively, these findings suggest that scriptaid and zebularine are potential anti-cancer drugs, either single or in combination, for the therapy of breast cancer. Further investigations of the gene regulatory pathways directed by scriptaid and zebularine are definitely warranted in the future.
Keywords: apoptosis